Perceptions and Efficacy of Oral Rinsing with Two Types of Coconut Oil: A Comparative Study - Peedikayil, Faizal C.; Diwaker, Neethu P.; P., Chandru T.; Kottayi, Soni (International Coconut Community, 2021)
This study focuses on the efficacy of virgin and regular coconut oil on plaque-related gingivitis and the perceptions of the subjects regarding its taste and odor. A study was carried out on 80 subjects, divided into 4 groups, 20 participants each. Group A: virgin coconut oil (VCO) gargling, Group B: regular cooking coconut oil (RCCO) gargling, Group C: chlorhexidine mouthwash gargling, and Group D: routine toothbrushing. The Modified gingival Index (MGI) was assessed to check the gingival inflammation on the 15th and 30th days. Perceptions of the subjects on the taste and odor were measured with the Hedonic Scale, and texture of VCO and RCCO in comparison with chlorhexidine. The baseline means MGI values are: 1.62±0.47, 1.74±0.22, 1.78±0.22, 1.68±0.66 for Group A, B, C, and D respectively. There is a significant difference in gingival index scores across all the study groups on the 15th day and 30th day (intra-group comparison). There is a significant difference in mean scores when group VCO, RCCO, and Chlorhexidine are compared with the control (inter-group comparison). Hedonic rating scale shows: chlorhexidine has a better odor (3.2) than VCO (3.1), RCCO (2.9). Chlorhexidine scored (3.4) in taste compared with VCO (3.1) and RCCO (2.8). Texture and mouthfeel scores for Chlorhexidine and VCO (3.6) and RCCO (3.4). VCO and RCCO are as efficient in reducing gingivitis. VCO has better taste, odor, and texture in the mouth than RCCO.